(untitled) (Bangladesh Journal of Botany, 2022)
A field experiment was conducted with 10 crop sequences as treatments to find out nutrient dynamics and nutrient uptake pattern. This study was laid out in randomized block design with three replications. Among the different cropping sequence taken under study, sudan fodder- berseem- cowpea fodder recorded highest nitrogen (443.6 kg/ha), phosphorus (146.8 kg/ha) and potassium (306.3 kg/ha) uptake followed by cowpea fodder- berseem- maize fodder with 411, 105.9 and 274 kg/ha nitrogen, phosphorus and potassium, respectively. Both these crop sequences showed negative nitrogen balance in soil. Meanwhile potassium balance was negative for most of the sequences. However, high value rice- capsicum - vegetable cowpea registered lowest nitrogen (134.5 kg/ha) and potassium uptake (129.20 kg/ha) leading to a positive nitrogen and potassium balance. Bangladesh J. Bot. 51(3): 607-613, 2022 (September)